2021
DOI: 10.1097/hp.0000000000001395
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Depleted Uranium-exposed Gulf War Veterans: More Evidence for Bone Effects

Abstract: Gulf War I veterans who were victims of depleted uranium (DU) “friendly-fire” incidents have undergone longitudinal health surveillance since 1994. During the spring of 2019, 36 members of the cohort were evaluated with a monitoring protocol including exposure assessment for total and isotopic uranium concentrations in urine and a comprehensive review of health outcomes, including measures of bone metabolism and bone mineral density (BMD) determination. Elevated urine U concentrations were observed in cohort m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The low-uU group is defined as those having uU < 0.1 μg U/g creatinine. 15,17,26 High exposure was defined as current uU concentrations ≥0.1 μg U/g creatinine, a value between 0.043 μg U/g creatinine (the 95% percentile reported for creatinine-adjusted uU concentrations in nonexposed populations in the United States) 27 and 0.35 μg U/L, which is reported as a uU upper limit that occurs naturally in areas with elevated U in water and food. 28…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low-uU group is defined as those having uU < 0.1 μg U/g creatinine. 15,17,26 High exposure was defined as current uU concentrations ≥0.1 μg U/g creatinine, a value between 0.043 μg U/g creatinine (the 95% percentile reported for creatinine-adjusted uU concentrations in nonexposed populations in the United States) 27 and 0.35 μg U/L, which is reported as a uU upper limit that occurs naturally in areas with elevated U in water and food. 28…”
Section: Methodsmentioning
confidence: 99%
“…An initial and now persistent finding over this 30-year follow-up is the excretion of elevated concentrations of urine uranium (uU) in those cohort members with retained metal fragments. 14–17 This observation indicates the systemic absorption of metal ions from embedded fragments, illustrating not only concern for local tissue effects, but toxic metal exposure of organ systems far from the site of the retained fragments.…”
Section: Depleted Uranium Surveillance Visitsmentioning
confidence: 95%
See 1 more Smart Citation
“…Otherwise, bone density is decreased, but the toxicity for kidney, liver and nerve system is increased. 20 , 28 , 29 Animal experiments also revealed that interstitial inflammation, fibrosis, edema, hemorrhage of the lung and emphysema can be induced by DU aerosol. 27 …”
Section: Wound Characteristicsmentioning
confidence: 99%